2019
DOI: 10.1029/2018jd028679
|View full text |Cite
|
Sign up to set email alerts
|

A New Parameterization of Volcanic Ash Complex Refractive Index Based on NBO/T and SiO2 Content

Abstract: Radiative transfer models used in remote sensing and hazard assessment of volcanic ash require knowledge of ash optical parameters. Here we characterize the bulk and glass compositions of a representative suite of volcanic ash samples with known complex refractive indices (n + ik, where n is the real part and k is the imaginary part). Using a linear regression model, we develop a new parameterization allowing the complex refractive index of volcanic ash to be estimated from ash SiO2 content or ratio of nonbrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…For this sample, we used the empirical relation obtained in Ref. [31] between the real part of the CRI and the weight percent of SiO 2 to obtain the a priori value of the anchor point. In the next section we come back to this relation.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…For this sample, we used the empirical relation obtained in Ref. [31] between the real part of the CRI and the weight percent of SiO 2 to obtain the a priori value of the anchor point. In the next section we come back to this relation.…”
Section: Research Articlementioning
confidence: 99%
“…The majority of satellite studies that report measurements of volcanic ash currently rely on CRI measurements made in the 1970s on bulk material [26,27,28]. It is well-known, however, that such measurements underestimate the contribution of scattering in aerosol [29][30][31]. In addition, it has been shown that the spectra observed by satellites cannot be reproduced by forward models relying on these indices, especially when the optical depth is large [32].…”
Section: Introductionmentioning
confidence: 99%
“…This is important because the main methods for detecting and quantifying ash in volcanic clouds rely on an infrared signature due to SiO 2 . With knowledge of the SiO 2 content or the ratio of non-bridging oxygen to the tetrahedrally-coordinated cations (NBO/T) and the glass and crystal amounts it is possible to select appropriate refractive indices to use for the scattering calculations needed in order to retrieve ash properties from infrared satellite measurements [40].…”
Section: Refractive Index and Compositionmentioning
confidence: 99%
“…These are ideal test cases, which do not include other aerosols or aqueous cloud. These spectra include six different atmospheres: high latitude, mid-latitude day and night, tropical daytime, and polar summer and winter (including atmospheric profiles created for the Michelson Interferometer for Passive Atmospheric Sounding, MIPAS; Remedios et al, 2007). The spectra were modelled using the refractive indices of samples of volcanic ash from the Eyjafjallajökull eruption in 2010 (Peters, 2010): the main eruption considered in this study.…”
Section: The Infrared Atmospheric Sounding Interferometermentioning
confidence: 99%
“…Acknowledgements. Five of the atmospheric profiles used for the channel selection are reference spectra for the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS; Remedios et al, 2007). The IASI spectra used in this study are available from the Centre for Environmental Data Analysis (EUMETSAT, 2009).…”
mentioning
confidence: 99%